Systems Medicine Disease: Disease Classification and Scalability Beyond Networks and Boundary Conditions - Berlin, Richard; Gruen, Russell; Best, James (Frontiers in Bioengineering and Biotechnology, 2018)
Abstract: In order to accommodate the forthcoming wealth of health and disease related information, from genome to body sensors to population, the approach to disease description and definition demands re-examination. Traditional classification methods remain trapped in historical profile; systems science which describes dynamic processes, adaptive response, and asynchronous communication channels must address disease in terms consistent with systems engineering. [1] Disease is to be viewed beyond the thresholds of lines and boundaries; it is not only the result of reductionist, mechanistic categories which reluctantly face re-composition. Disease is process and synergy as Systems Biology proceeds to Systems Medicine, no longer confined to a single spatial biologic level or considered stationary despite fluctuation across simultaneous time in nanoseconds, minutes and years. [2] [3]